World Development Report 2004 : Making Services Work for Poor People - World Bank (World Bank, 2012)
Too often, services fail poor people in access, in quality, and in affordability. But the fact that there are striking examples where basic services such as water, sanitation, health, education, and electricity do work for poor people means that governments and citizens can do a better job of providing them. Learning from success and understanding the sources of failure, this year’s World Development Report, argues that services can be improved by putting poor people at the center of service provision. How? By enabling the poor to monitor and discipline service providers, by amplifying their voice in policymaking, and by strengthening the incentives for providers to serve the poor. Freedom from illness and freedom from illiteracy are two of the most important ways poor people can escape from poverty. To achieve these goals, economic growth and financial resources are of course necessary, but they are not enough. The World Development Report provides a practical framework for making the services that contribute to human development work for poor people. With this framework, citizens, governments, and donors can take action and accelerate progress toward the common objective of poverty reduction, as specified in the Millennium Development Goals.